Psychosomatic interactions in kidney transplantation: role of personality dimensions in mental health-related quality of life - Federica Guerra; Jessica Ranieri; Domenico Passafiume; Diana Lupi; Daniela Maccarone; Francesco Pisani; Claudio Ferri; Dina Di Giacomo (SAGE Publishing, 2021)
Background and aims: The increase in innovative and personalized medicine solutions in kidney surgery can improve patients' chances of survival; however, during the transplantation process, patients are exposed to many psychological challenges. This study aimed to evaluate the role and impact of personality dimensions on the behaviour of waiting-list patients towards the post-surgery adaptation process. Method: The participants were 113 out-patients aged 18-70 years (mean age 54.7 years, SD ± 9.9) who had received a kidney transplant at least 3 years prior to the study. Results: The results of the study revealed that personality dimensions can predict mental health-related quality of life after kidney transplantation; in particular, the dimensions play an important role in patients' behavioural ability to manage their quality of life both during end-stage renal disease and after kidney transplantation. Psychological distress and anxiety were associated with a low level of the conscientiousness dimension, while a high level of the openness dimension was associated with a high level of psychological distress and stress. In addition, body self-perception was associated with personality dimensions. Conclusion: Personality dimensions were found to predict behavioural reactions when emotional traits and body self-perception for each patient were combined; clinical psychologists could apply personalized intervention by modeling the treatments step by step and mitigating the negative effects of the whole kidney transplantation disease, thus helping the individual to adapt to a new life.